2015
DOI: 10.1097/mao.0000000000000523
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Classification of Superior Canal Dehiscence

Abstract: CT scans were assessed for (1) superior canal dehiscence or "near" dehiscence, (2) defect location relative to the skull base, (3) surrounding tegmen defects, (4) geniculate ganglion dehiscence, (5) superior petrosal sinus-associated dehiscence (SPS), (6) low-lying tegmen, and (7) the distance between the outer table of the temporal bone and the arcuate eminence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 25 publications
3
53
2
1
Order By: Relevance
“…Lookabaugh et al studied 392 temporal bones in 202 patients with symptomatic SSCD and found that the most common location of the dehiscence was the arcuate eminence (59.2%), followed by the medial downslope of the semicircular canal (28.8%), then the lateral upslope of the semicircular canal (7.6%). 22 The same study also reported that the arcuate eminence was found an average of 26.41 mm (range: 17.6-38.5) from the outer cortex of the temporal bone.…”
Section: Discussionmentioning
confidence: 75%
“…Lookabaugh et al studied 392 temporal bones in 202 patients with symptomatic SSCD and found that the most common location of the dehiscence was the arcuate eminence (59.2%), followed by the medial downslope of the semicircular canal (28.8%), then the lateral upslope of the semicircular canal (7.6%). 22 The same study also reported that the arcuate eminence was found an average of 26.41 mm (range: 17.6-38.5) from the outer cortex of the temporal bone.…”
Section: Discussionmentioning
confidence: 75%
“…First, specimens in this study were prepared with defects of 0.5–3.5 mm in size over the arcuate eminence; however, SCD defects do vary in anatomical size, location and shape. The slope of the tegmen at the defect and its location along the canal influences the surgical approach 30 , which can in turn affect the orientation from which a surgeon repairs a defect. This has implications for the consequential position of wax, and volume of wax necessary to achieve a stable occlusion of the canal.…”
Section: Discussionmentioning
confidence: 99%
“…Since the normal stapedo-vestibular joint space is not always seen as a distinct space on high resolution CT, it may not be possible to confirm these pathologic changes on CT. CT is still useful in the evaluation of patients with suspected NOG related hearing loss, however, as CT can identify other etiologies of conductive hearing loss, including malleus fixation, otosclerosis, and third window syndromes. 15,16 …”
Section: Discussionmentioning
confidence: 99%